2015
DOI: 10.1590/0034-7167.2015680121i
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnoses and interventions for a child after cardiac surgery in an intensive care unit

Abstract: Objective: to describe the nursing clinical judgment as a basis for ND identifi cation and development of a NIC treatment plan for a child after cardiac surgery under intensive care. Method: a case study with data retrospectively collected from charts. Results: Three nurses identifi ed NANDA-I diagnoses and NIC interventions. A 6-month-old child submitted to cardiac surgery, requiring extracorporeal membrane oxygenation in the postoperative period. Four main nursing diagnoses were identifi ed, towards which te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
12
0
3
Order By: Relevance
“…In this sense, the elaboration and use of care plans implies the representation of guiding instruments for the management of nursing care, as it favors the decision-making process, assisting patients in all their complexity (13) . It is worth mentioning that the results are directed to hospitalized patients and do not apply to patients seen at the outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the elaboration and use of care plans implies the representation of guiding instruments for the management of nursing care, as it favors the decision-making process, assisting patients in all their complexity (13) . It is worth mentioning that the results are directed to hospitalized patients and do not apply to patients seen at the outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pediatric infection has grown in recent years, with the increase in invasive procedures, technological development, and the indiscriminate use of antimicrobials. (10) A study in Fortaleza (CE) with 270 diagnostic assessments in children with congenital heart disease found impaired gas exchange (91.5%) to be the most frequent ND, and the most prominent related factor was ventilation-perfusion imbalance (89.5%). (9) Such evidence is consistent with the data shown in this study, in which children received this diagnosis, often due to the same related factor.…”
Section: Discussionmentioning
confidence: 99%
“…Table (10) showed that children in study group were exposed to post CC bleeding less than children in the control group (3.3% & 16.7% in order). As regarded to child's pulse in the affected limp, it was found in the current study that vast majority (93.3%) of children in study group don't have weak or absent pulse, while half (50%) of children in control group have weak or absent pulse.…”
Section: It Was Evident Frommentioning
confidence: 93%
“…Nurses must be knowledgeable about the human responses of these children; many of their responses are physiological, yet there are a multitude of psychosocial, behavioral and family responses that are also very important for the nurse to understand, diagnose and treat. A thorough nursing assessment to identify signs and symptoms provides data critical to identifying nursing-sensitive human responses, and their etiologies; these are the clinical indicators of nursing diagnoses [10] .…”
Section: Introductionmentioning
confidence: 99%